2020
DOI: 10.1016/j.prosdent.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reproducibility of the chemical solubility of dental ceramics using ISO 6872:2015

Abstract: Statement of problem. The current chemical solubility method in the International Standards Organization (ISO) 6872 (2015) specifies only the total surface area of specimens for testing (≥30 cm 2) but does not describe the morphology or geometry. This could impact the reproducibility of the test outcomes. Purpose. The purpose of this in vitro study was to investigate the factors influencing the reliability of the ISO 6872:2015 'Dentistry-Ceramic materials' test for chemical solubility. Material and methods. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Divalent Mg +2 , Ca +2 , Zn +2 , and Ba +2 , trivalent Al +3 and, immobile Zr ions increase chemical stability and decrease ion exchange 24,26 . Accordingly, feldspathic and lithium disilicate porcelain have been reported to be less stable than zirconium core structures 17 . Slightly soluble materials are considered to have low surface roughness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Divalent Mg +2 , Ca +2 , Zn +2 , and Ba +2 , trivalent Al +3 and, immobile Zr ions increase chemical stability and decrease ion exchange 24,26 . Accordingly, feldspathic and lithium disilicate porcelain have been reported to be less stable than zirconium core structures 17 . Slightly soluble materials are considered to have low surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 Accordingly, feldspathic and lithium disilicate porcelain have been reported to be less stable than zirconium core structures. 17 Slightly soluble materials are considered to have low surface roughness. Karakaya and Cengiz-Yanardag reported that the materials containing zirconium showed least roughness, where they examined the roughness of materials exposed to different concentrations of bleaching agents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations